Antonio Rinaldi. Un intellettuale nella cultura del Novecento - Bartolini, Francesca (Premio Ricerca «Città di Firenze», 2014)
Antonio Rinaldi, un intellettuale nella cultura del Novecento (Antonio Rinaldi, an intellectual in twentieth century culture) gives new shape the figure of an artist who is only apparently of secondary importance, starting from the work and documents preserved in a previously unpublished archive. The work traces the fundamental stages of the life and work of the writer focusing on the years of his university education, which are fundamental for the relationships he forged (with Roberto Longhi and Giorgio Morandi, as well as with fellow students Attilio Bertolucci, Giorgio Bassani, Lanfranco Caretti, Francesco and Gaetano Arcangeli and the student Pier Paolo Pasolini). An appendix of unpublished texts proposes the two-part correspondence with his teacher Giuseppe Raimondi and his friend Giuseppe Dessí.